Powered Ambulance Cots: Effects of design differences on muscle activity and subjective perceptions of operators. (September 2013) - Sommerich, CM; Lavender, SA; Umar, RZ Radin; Park, SH; Li, J; Dutt, M
An experiment was conducted in order to examine the effect of differences in the design of two powered ambulance cots on operators. Experienced EMS workers performed two common tasks, loading and unloading the cots from a simulated ambulance bed. Dependent measures included muscle activity (trunk, shoulder, and arm muscles) and subjective perceptions. Independent variables were cot (Cot R and Cot Y), and weight on the cot (100, 150, and 200 lbs., to simulate patients of different weights). Muscle activity was found to be significantly lower when using Cot R, for both tasks, in comparison to Cot Y. Subjective preferences were mixed, with many subjects preferring the handle design of Cot Y, while preferring Cot R overall. This study showed that it is possible to substantially reduce the physical stress imposed on operators when loading and unloading a cot to and from an ambulance through improvements in cot design.